Speciation of Candida using CHROMagar isolated from Various Clinical Samples - DC, Shwetha; D., Venkatesha (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Infections due to Candida especially Non-albicans Candida (NAC) species are increasingly being reported in recent years. Isolation and identification up to species level are of utmost importance in the early management of these infections. Materials and methods: All the clinical samples received in the Microbiology laboratory were inoculated on to Blood agar and MacConkey agar. The isolates which revealed Gram-positive budding yeast cells on Gram staining were further inoculated on to SDA (Sabouraud Dextrose agar) and Hicrome Candida differential agar. Candida was differentiated into species based on color and morphology on Hicrome agar. Result: A total of 126 Candida were isolated from various clinical samples. C.Albicans was the most common species isolated (49.2%) followed by C. tropicalis (19.8%), C. glabrata (19%), and C. krusei (12%). Conclusion: Hicrome agar is a simple, rapid, and cost-effective medium for the speciation of Candida.